Pterygium Surgery with Conjunctival Autograft without Suture or Fibrin Glue - Indira Silviandari (Majalah Oftalmologi Indonesia, 2016)
Background: To research the efficacy of pterygium excision with conjunctival autograft withoutsuture or fibrin glue.Methods: After pterygium excision and preparing of autologous conjunctival graft, the recipient bedis encouraged to achieve natural haemostasis before graft placement. Excessive haemorrhage in thegraft bed is tamponaded without cautery. Graft adherence and positioning is examined 15 minutesafter surgery. Cases were reviewed to obtain details of complications and recurrence.Results: Twenty seven eyes of 27 patients with pterygium underwent conjunctival autograft withnatural patient’s own blood acting as bioadhesive or fixative, without suture. The mean age is 54 yearsold (SD 9.86), 13 males and 14 females. Mean follow up time was 4.0 months (SD 1.85). The rate ofrecurrences which followed up for 6 months is 8.33% (1 patient), 9.09% (1 patient) which followed upfor 3 months and no recurrences in patients which followed up for 1 month. The complicationsregarding graft displacement was 2 patients (7.4%), 2 patients with graft retraction (7.4%), and 1patient with loss of graft (3.7%). The other complications were not found and cosmesis was excellent.Conclusion: This study suggests that autologous fibrin in blood works as bioadhesive and can be usedas alternative method for graft fixation in pterygium surgery.